Evolution of cognitive networks and self-adaptive communication systems - Lagkas, Thomas D.; Sarigiannidis, Panagiotis; Louta, Malamati; Chatzimisios, Periklis (Information Science Reference, an imprint of IGI Global, 2013)
"This book overviews innovative technologies combined for the formation of self-aware, self-adaptive, and self-organizing networks, for those interested in clarifying the latest trends toward a unified realization for cognitive networking and communication systems"...Provided by publisher
Keywords: Cognitive radio networks; Telecommunication systems; Adaptive signal processing; Opportunistisches Netzwerk; Adaptive Signalverarbeitung; Mobile Telekommunikation; Aufsatzsammlung